Pelatihan Kesiapan Diri menuju Pernikahan bagi Dewasa Muda di Gereja GKI Gejayan - Christina Claudia; Sandra Handayani Sutanto; Giofanny Jessica Kaparang; Vanessa Celesta (Fakultas Psikologi Universitas Pancasila, 2024)
Young adulthood is a life stage where one develops romantic relationships culminating in marriage and forming one’s own family. However, recent trends suggest that starting and maintaining healthy marriage relationships may be challenging in Indonesia, indicating a low marital readiness amongst young adults. Several factors that impact one’s marital readiness include family life knowledge, coming to terms with family-of-origin issues, emotional intelligence and communication skills. Therefore, training that addresses these factors amongst young adults can help prepare them for a healthy marriage. Komisi Dewasa Muda at GKI Gereja Gejayan, who serves young adults in the Sleman area found this issue in their young adult community. Through this training, the young adults in the Sleman area may be equipped to enter marriage well and to develop, as well as maintain a healthy marriage relationship moving forward. The evaluation of the training also indicates that the materials provided were relevant to adult marriage preparation, had a positive impact, and were delivered using an engaging approach.